ASSESSING THE SUCCESS OF FARMERS’ ASSOCIATIONS: THE CASE OF BAYBAY CITY, LEYTE, PHILIPPINES - Valenzona, Raian Mark P; Amestoso, Nilda T; Casinillo, Leomarich F (Journal of Agriculture and Technology Management, 2020)
This research study assessed the internal functions and external factors affecting the success of farmers’ associations (FAs) in Baybay City, Leyte, Philippines which were registered as vegetable producers. A total of twenty (20) FA officers, 68 FA members and one (1) city agriculture technician comprised the respondents of the study. Two survey methods were used, namely: the Key Informants Interview (KII) to gather data related to external factors with city agriculture technician and a structured questionnaire to gather internal factor- related data with FA members and FA officers. Mean, standard deviation, and percentages were used to describe the internal and external factors affecting the FAs. Correlation analysis was also applied to determine the relationship of the internal factors and external factors to the success of FAs.  Results showed that 53% of FAs were 3 to 4 years in existence with an average of 29 members; 68% of them were women. FA members indicated high satisfaction rate on FAs’ functions for provision of technical information, and provision of inputs. Results revealed that FAs’ equity growth rate increased from 32.92% in 2014-2015 to 81.65% in 2017-2018. Findings of the study revealed a significant relationship between internal factors namely leadership, building capacities, cooperation of other organizations and FAs’ success of FAs. The external factors namely political factors (government programs) and economic factors (input costs) were found to have significant effect on FAs’ success. Hence, human resource mobilization skill needs to be additionally built up in order to stimulate more participation and responsibility from farmers.